Drugie oblicze biblioteki – inicjatywy edukacyjno-kulturalne w Bibliotece Uniwersytetu Łódzkiego - Michalska, Urszula; Osiewała, Renata (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
The common definition of the library concept usually consists of three basic functions: gathering, storing and sharing. In the case of the academic library we also take a specific user into consideration, the academic community. This is the main group that the library is aimed at. Scientific libraries are seeking to change this stereotype by fetching its readers not only possibility of reaching interesting literature but also a wide range of cultural initiatives. This article presents initiatives taken by The Library of the University of Lodz in 2016, in order to fit in with the programme of spreading readership and promoting libraries by many events encouraging to visit this institution regularly.